Evolution, Expression and Functional Analysis of CXCR3 in Neuronal and Cardiovascular Diseases: A Narrative Review - Satarkar, Devi; Patra, Chinmoy (Frontiers in Cell and Developmental Biology, 2022)
Chemokines form a sophisticated communication network wherein they maneuver the spatiotemporal migration of immune cells across a system. These chemical messengers are recognized by chemokine receptors, which can trigger a cascade of reactions upon binding to its respective ligand. CXC chemokine receptor 3 (CXCR3) is a transmembrane G protein-coupled receptor, which can selectively bind to CXCL9, CXCL10, and CXCL11. CXCR3 is predominantly expressed on immune cells, including activated T lymphocytes and natural killer cells. It thus plays a crucial role in immunological processes like homing of effector cells to infection sites and for pathogen clearance. Additionally, it is expressed on several cell types of the central nervous system and cardiovascular system, due to which it has been implicated in several CNS disorders, including Alzheimer’s disease, multiple sclerosis, dengue viral disease, and glioblastoma, as well as cardiovascular diseases like atherosclerosis, Chronic Chagas cardiomyopathy, and hypertension. This review provides a narrative description of the evolution, structure, function, and expression of CXCR3 and its corresponding ligands in mammals and zebrafish and the association of CXCR3 receptors with cardiovascular and neuronal disorders. Unraveling the mechanisms underlying the connection of CXCR3 and disease could help researchers investigate the potential of CXCR3 as a biomarker for early diagnosis and as a therapeutic target for pharmacological intervention, along with developing robust zebrafish disease models.